Analisis kesulitan belajar siswa dalam menyelesaikan soal cerita materi perkalian desimal kelas V SDN Cihandeuleum - Widari Saripah; Winarti Dwi Febriani; Riza Fatimah Zahrah (IKIP Siliwangi, 2026)
Understanding mathematical concepts is not only demonstrated through computational skills, but also through the ability to solve word problems that require students to comprehend the context, translate information, and select the appropriate mathematical operations. However, in reality, many fifth-grade elementary school students struggle to solve word problems, particularly those involving decimal multiplication. These difficulties include understanding the problem, performing calculations, and arriving at systematic solutions. Based on this phenomenon, this study aims to analyze the types and factors that contribute to students’ difficulties in solving word problems related to decimal multiplication.This research employs a qualitative descriptive method involving nine fifth-grade students at SDN Cihandeuleum as subjects. Data were collected through word problem tests, observation, documentation, and in-depth interviews with students experiencing difficulties. The findings of this study are expected to provide a concrete picture of where students face difficulties and serve as a foundation for developing more targeted instructional strategies. Keywords: learning difficulties, word problems, decimal multiplication, elementary students, error analysis